BUDAYA SEKOLAH BERLANDASKAN NILAI KASIH SAYANG MELALUI KURIKULUM CINTA DALAM PEMBENTUKAN KARAKTER SOSIAL SISWA DI MA MISBAHUL FATA - Nurus Syahidatul Qushwa; Abdul Aziz Wahab; Mahfudz Sulaiman (STKIP Pesisir Selatan, 2026)
This study analyzes the practice of a school culture based on the value of compassion through the implementation of the Love Curriculum, describes the process of internalizing the value of compassion in the formation of students' social character, and identifies supporting and inhibiting factors in its implementation at MA Misbahul Fata. Using a qualitative approach and case study design, data were collected through observation, in-depth interviews, and documentation analysis. Data validity was tested through triangulation and analyzed using the Miles and Huberman interactive model. The results show that a school culture based on the value of compassion is realized through habituation, role models, religious activities, and humanistic social interactions. This process encourages the development of empathy, social responsibility, and mutual respect in students. Its implementation is supported by the commitment of the school community, a religious madrasah environment, and parental support, but still faces obstacles such as differences in student backgrounds and limited supervision outside the school. This study offers a study on the implementation of the Love Curriculum as the basis of a school culture based on the value of compassion in the formation of students' social character, by emphasizing the process of internalizing values ​​through social interactions and continuous habituation of the school culture.